2005
DOI: 10.1080/02841850510016018
|View full text |Cite
|
Sign up to set email alerts
|

MRI combined with MR cholangiopancreatography versus helical CT in the evaluation of patients with suspected periampullary tumors: a prospective comparative study

Abstract: MRI with MRCP was significantly more accurate than CT in differentiating between malignant and benign lesions in patients with suspected periampullary tumors, mainly due to the information obtained on the MRCP images of the biliary and pancreatic duct anatomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
1
5

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 29 publications
2
23
1
5
Order By: Relevance
“…Andersson M et al, [16] concluded in their study that MRI with MRCP was more accurate than CT in differentiating between malignant and benign lesions in patients with suspected periampullary tumors. This is consistent with present study where MRI/MRCP showed 100 % accuracy in diagnosing cases with periampullary carcinoma.…”
Section: Benign Stricturementioning
confidence: 99%
“…Andersson M et al, [16] concluded in their study that MRI with MRCP was more accurate than CT in differentiating between malignant and benign lesions in patients with suspected periampullary tumors. This is consistent with present study where MRI/MRCP showed 100 % accuracy in diagnosing cases with periampullary carcinoma.…”
Section: Benign Stricturementioning
confidence: 99%
“…MRI with MRCP represents one of the most comprehensive imaging examinations currently available for evaluating periampullary obstruction. MRCP can outline the morphology of the bile and pancreatic ducts, and conventional MRI may improve the specificity of MRCP by allowing observation of periductal masses and pancreatic parenchymal abnormalities [8,9,20]. An earlier study suggested that MRI combined with MRCP was a more accurate technique than CT in differentiating between malignant and benign lesions in patients with suspected periampullary tumours.…”
Section: Discussionmentioning
confidence: 98%
“…Patients with bile duct stones were excluded because biliary calculi are strongly associated with benign obstructions and require choledocholithotomy or endoscopic management [4]. The inclusion criteria were as follows: (1) a dilatation of bile duct must be present, one that was more than 7 mm of the extrahepatic ducts in patients<60 years of age and 10 mm in patients with cholecystectomy [9] accompanying clinical findings (including right upper quadrant abdominal pain, jaundice, elevated total serum bilirubin, and/or phosphatase levels); (2) both nonenhanced dual-phase enhanced CT combined with nCTCP and MR with MRCP examinations had to be performed before the operation; (3) both CT and MR image qualities were diagnostic; (4) direct cholangiography, such as ERCP or percutaneous transhepatic cholangiography (PTC) must be performed after both CT and MRI; and (5) final clinical diagnoses based on surgical specimens, biopsy under laparotomy, ERCP, and CT or MRI follow-up>12 months for the enrolled patients must be available. 139 patients were excluded from the study for one of the following reasons: (1) neither CT nor MR examinations (n=15) or incomplete CT or MR examinations (n=5); (2) only CT without MR examinations (n=57) or only MR without CT examinations (n=38); (3) both thick-slab and 3D MRCP image qualities were not diagnostic, in which a severe respiratory motion artefact affected the diagnostic evaluation (n=6); (4) direct cholangiography performed before CT or MRI (n=3); and (5) final clinical diagnoses were not established (n=15).…”
Section: Patient Selectionmentioning
confidence: 99%
See 2 more Smart Citations